Impact of student-centered strategies on vocabulary learning in a foreign language classroom - Cummings, Mandy (My University, 2013)
The traditional middle school foreign language classroom typically has the teacher imparting the knowledge and vocabulary of the unit to the class. The students are unmotivated to take ownership of their learning with this methodology and are highly dependent on the teacher for the information. They do not view themselves as capable of finding and or sharing vocabulary in the secondary language. The author of this study felt that this mentality needed to shift from the "sage on the stage" to the students becoming empowered learners. The question that arises is how to achieve this. Could student centered vocabulary learning have an impact in a foreign language classroom? What are the best ways to implement the shift of power? The author facilitated this shift by utilizing student created word expert cards that emphasized the new, unfamiliar vocabulary from the next unit of study within a curriculum textbook. When students had control of one of the new words, they were then in charge of teaching each other the new vocabulary through peer tutoring as the teacher acted as a mediator. This effectively reversed the power roles. The teacher also shifted control by implementing semantic mapping activities of the vocabulary words with the students, justifying their reasoning for word placement and usage with each other; the teacher once again acted as a mediator. Data was collected through student interviews, student surveys, and end of the unit vocabulary tests. The results of the study show that students felt they were in control of their learning, took pride in both knowing a word in the target language before everyone else and sharing that knowledge with their peers. Vocabulary comprehension and maintenance improved through the use of the semantic mapping activities versus the traditional call-out review. The conclusion of the study is that student-centered vocabulary instruction improves the motivation and ownership of students. The implementation of the vocabulary learning strategies not only assisted with the retention of the second language vocabulary but it also instilled within the students a sense of pride that they could learn a foreign language and not be dependent upon the teacher.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. [33] leaves. Includes bibliographical references (leaves [32-33]).
Keywords: Student centered vocabulary instruction; Spanish language--Study and teaching (Middle school)--Vocabulary; Spanish language--Study and teaching (Middle School); Vocabulary learning; Spanish language